Inhibition of the Low Molecular Weight Protein Tyrosine Phosphatase (LMPTP) as a Potential Therapeutic Strategy for Hepatic Progenitor Cells Lipotoxicity—Short Communication - Alicka, Michalina (Int J Mol Sci, 2019)
Equine metabolic syndrome (EMS) is a cluster of metabolic disorders, such as obesity, hyperinsulinemia, and hyperleptinemia, as well as insulin resistance (IR). In accordance with the theory linking obesity and IR, excessive accumulation of lipids in insulin-sensitive tissues (lipotoxicity), like liver, alters several cellular functions, including insulin signaling. Therefore, the purpose of the study was to isolate equine hepatic progenitor-like cells (HPCs) and assess whether inhibition of low molecular weight protein tyrosine phosphatase (LMPTP) affects the expression of genes involved in macroautophagy, chaperone-mediated autophagy (CMA), endoplasmic reticulum stress, and mitochondrial dynamics in a palmitate-induced IR model. We demonstrated that LMPTP inhibition significantly enhanced expression of heat shock cognate 70 kDa protein (HSC70), lysosome-associated membrane protein 2 (LAMP2), and parkin (PRKN), all master regulators of selective autophagy. We also observed downregulation of C/EBP homologous protein (CHOP), activating transcription factor 6 (ATF6) and binding immunoglobulin protein encoded by the HSPA gene. Moreover, LMPTP inhibition increased alternative splicing of X-box binding protein 1 (XBP1), suggesting high endonuclease activity of inositol-requiring enzyme 1 alpha (IRE1α). Taken together, our data provide convincing evidence that LMPTP inhibition reverses palmitate-induced insulin resistance and lipotoxicity. In conclusion, this study highlights the role of LMPTP in the regulation of CMA, mitophagy, and ER stress, and provides a new in vitro model for studying HPC lipotoxicity in pre-clinical research.